The correlation between stress level and eating disorder syndrome in preclinical medical students at Faculty of Medicine and Veterinary Medicine, University of Nusa Cendana, Kupang, East Nusa Tenggara - Djema, Marceline Consolatrix Cheyene; Sagita, Sidarta; Woda, Rahel Rara; Legoh, Dickson (Universitas Gadjah Mada, 2023)
Nowdays with various kinds of needs and demands in life that must be met at any time can cause stress of someone. Medical students are often experience high level of stress due to the demands of high education standards requirements. Continous chronic stress can affect eating behaviour lead to the potential cause of eating disorder syndrome (EDS). This study aimed to evaluate the correlation between stress level and EDS in preclinical medical students of Nusa Cendana University, Kupang, East Nusa Tenggara. It was an analytic observational with a cross sectional design conducting on the preclinical medical students by filling out depression anxiety stress Scale (DASS-42) and eating attitude test (EAT-26) questionnaires. Respondents were selected by the probability sampling method with a stratifies random sampling technique. A total 141 respondents who met the inclusion and exclusion criteria were recruited. Bivariate analysis by using the Wilcoxon Theta correlation test was performed. Among respondents involved in this study, 13 (9.2%) respondents did not experience stress and 128 (90.8%) experienced stress including 43 (30.5%) mild stress, 68 (48.3%) moderate stress, and 17 (12.3%) severe stress. The EDS was observed in 15 (10.6%) respondents. A significant moderate correlation between stress level and EDS was indicated (θ = 0.58). In conclusion, there is correlation between stress level and EDS on preclinical medical students of Nusa Cendana University, Kupang.